Educational actions to promote the value of responsibility in students of the 9th grade of school complex nº 187-lubango-huíla.(Original) (Revista científica Olimpia, 2020)
This article intends to present the results of the study carried aut at School Compex No. 187, Lubango-Huila and aims to develop educational actions for the formation of the value responsability in students. This research starts from the need to improve students behavior in Physical Education classroom and at the same time promote discipline in other matters that are not practical within the school. The result will be a tool that the Physical Education  professional can use in their classes and in this way support the work in values education that is carried aut by all the teachers in the school whith family and development involvement of the students in society in general.
Keywords: educação em valores; valor responsabilidade.